Destrucción de mosaicos mitológicos por los cristianos - López Monteagudo, Guadalupe; Blázquez Martínez, José María (Antigüedad y Cristianismo, 1990)
The destruction of the pagan works of art by the Christians, verified in numerous occasions by the ancient authors, is confirmed in various Roman mosaics in the Iberian Peninsula. In these it is posible to appreciate an intentional desire to erradícate certain scenes with mythological contexts, and this type of destruction has also been verified in mosaics found in other parts of the Empire. Of the twelve examples cited by the authors, 10 correspond to Bacchical scenes which surely means a reaction against the rebirth of the paganism and particularly of the cults of Venus and Bacchus which took place at the end of the fourth century in the north of África.